2017
DOI: 10.1002/ecs2.1948
|View full text |Cite
|
Sign up to set email alerts
|

Direct and context‐dependent effects of light, temperature, and phytoplankton shape bacterial community composition

Abstract: Citation: Paver, S. F., and A. D. Kent. 2017. Direct and context-dependent effects of light, temperature, and phytoplankton shape bacterial community composition. Ecosphere 8(9):e01948. 10. 1002/ecs2.1948 Abstract. Species interactions, environmental conditions, and stochastic processes work in concert to bring about changes in community structure. However, the relative importance of specific factors and how their combined influence affects community composition remain largely unclear. We conducted a multif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…A previous study dealing with the role of temperature showed a faster bloom development at warmer temperatures as well as a shift of bacterial community structure (BCS) towards the appearance of additional taxa [29]. Interestingly, a simultaneous study of temperature and light effects on bacterial communities' composition indicated that light effects are more likely to be direct, while those of temperature are mediated by phytoplankton [20]. We expect that although prokaryoplankton communities are initially similar in all mesocosms, they will subsequently diverge, and specific taxa are likely to emerge following the quantitative and qualitative changes of phytoplankton assemblages or due to direct effects of light.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A previous study dealing with the role of temperature showed a faster bloom development at warmer temperatures as well as a shift of bacterial community structure (BCS) towards the appearance of additional taxa [29]. Interestingly, a simultaneous study of temperature and light effects on bacterial communities' composition indicated that light effects are more likely to be direct, while those of temperature are mediated by phytoplankton [20]. We expect that although prokaryoplankton communities are initially similar in all mesocosms, they will subsequently diverge, and specific taxa are likely to emerge following the quantitative and qualitative changes of phytoplankton assemblages or due to direct effects of light.…”
Section: Introductionmentioning
confidence: 94%
“…Light as a driver of ecosystem dynamics has been explored in a number of studies, but has generally received less attention compared to other environmental factors like temperature and nutrients. It has been shown, however, that light may have direct or indirect effects at cellular to community levels [17][18][19][20]. For instance, stimulation of bacterial clades containing aerobic anoxygenic phototrophs (Rhodobacteraceae and NOR5) and inhibition of SAR11 [21][22][23] have been shown.…”
Section: Introductionmentioning
confidence: 99%
“…Various environmental factors, such as temperature, turbulence, nutrient concentrations and light, shape the fate of phytoplankton-bacteria interactions. Shifts from carbon commensalism to competition for inorganic nutrients are often observed when nutrients availability becomes limited (18)(19)(20)(21). The effect of light is, on the other hand, usually considered to be indirect via phytoplankton-bacterial coupling (22), and studies on the direct effect typically focus on UV radiation (23).…”
mentioning
confidence: 99%
“…The effect of light is, on the other hand, usually considered to be indirect via phytoplankton-bacterial coupling (22), and studies on the direct effect typically focus on UV radiation (23). Nevertheless, direct effects of light on bacterial communities have also been suggested to exist (21,24) and may be mediated by physiological responses of photoheterotrophic bacteria, such as rhodopsin-containing bacteria or aerobic anoxygenic phototrophic (AAP) bacteria. These organisms utilize energy from light for ATP synthesis but require organic carbon for growth (25).…”
mentioning
confidence: 99%
“…For example, in lakes, both phytoplankton biomass (Luria et al 2017) and physicochemical environmental conditions (Adamovich et al 2019; Liu et al 2015) influence the species composition of bacterial communities. Understanding the response of bacterial communities to the seasonal changes of the abiotic environment, including changes in the phytoplankton species composition, are necessary to understand changes in species composition or the functional roles of the bacterial communities in lakes (Gilbert et al 2012; Luria et al 2017; Paver and Kent 2017; Yannarell and Triplett 2005).…”
Section: Introductionmentioning
confidence: 99%